Development Of Electric Bus Real-Time Driving Cycle: A Case Study Of Pune, India (International Journal of Environmental Sciences, 2025)
The development of region-specific driving cycles is critical for accurate energy consumption estimation, battery sizing, and performance evaluation of electric buses. This study focuses on the creation of a real-time driving cycle tailored to urban driving conditions in Pune, India. High-resolution vehicle data, including speed and time, were collected from operational electric buses plying on representative city routes. The collected data was analyzed to determine key driving parameters such as average speed, acceleration, deceleration, idle time, cruise and stop frequency. A representative driving cycle was constructed using micro-trip segmentation and statistical methods to ensure it closely reflects actual traffic and operational conditions in Pune. The developed cycle was validated by comparing its characteristics with standard national and international driving cycles. This study highlights the importance of localized driving cycles for accurate electric vehicle performance assessment and contributes to better planning and deployment of electric buses in Indian urban environments.